IAENG Transactions on Engineering Technologies Special Issue of the International MultiConference of Engineers and Computer Scientists 2012 - Yang, Gi-Chul.; Ao, Sio-Iong.; Huang, Xu.; Castillo, Oscar; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
This volume contains revised and extended research articles written by prominent researchers participating in the conference. Topics covered include engineering physics, communications systems, control theory, automation, engineering mathematics, scientific computing, industrial engineering, and industrial applications. IAENG Transactions on Engineering Technologies: Special Issue of the International MultiConference of Engineers and Computer Scientists 2012 offers the state of art of tremendous advances in engineering technologies and physical science and applications, and also serves as an excellent reference work for researchers and graduate students working with/on engineering technologies and physical science and applications.
1 On Turbulence Transition In Three-dimensional Boundary Layer Flow -- 2 Efficient Algorithms For The Green's Function Formalism Semiconductor Transport Simulations On CPUS And GPUS -- 3 Performance Evaluation Of Check-By-Voting For Colluding Attack In Volunteer Computing Systems -- 4 Fast Slot Planning Using Constraint-Based Local Search -- 5 Sequencing Of Arrival Aircraft With Operational Constraints -- 6 Synchronized Triomineering On Rectangular Boards -- 7 Robust Portfolio Selection Model With Random Fuzzy Returns Based On Arbitrage Pricing Theory And Fuzzy Reasoning Method -- 8 Hierarchical Multiobjective Stochastic Linear Programming Problems Through A Fractile Optimization Model Using Reference Membership Intervals -- 9 Subsidy, Revenue And Tragedies In Heterogeneous Communities -- 10 A Game Theoretical Analysis For The Quantity Discount Problem With Weibull Ameliorating Items -- 11 Simulation Study Of An Integrated Reverse Logistics In Fuzzy Environment -- 12 A Hybrid-Heuristic For K-Minimum Spanning Tree Problems -- 13 An Optimal Model Of Adding Relation Between The Top And A Member Of A Linking Pin Organization Structure With K Subordinates -- 14 An Agri-Food Supply Chain Model To Empower Farmers For Supplying Deteriorated Product To Modern Retailer -- 15 Fuzzy Logic Approach To Inventory Lot-Sizing Problem Under Uncertain Environment -- 16 A Semantic Wiki To Support Knowledge Sharing In Innovation Activities -- 17 Overall Equipment Effectiveness Measurement - Weighted Approach Method & Fuzzy Expert System -- 18 A Supplier-Manufacturer Model For Procurement Plan In Export Oriented Furniture Industry With Sustainability Considerations -- 19 Statistical Analysis Of Friction Stir Weld Data -- 20 Development And Evaluation Of An Online Casebook For Teaching And Learning Of Industrial Accidents -- 21 Comparison Of Response To Visual And Auditory Digit Cues In Man-Machine System -- 22 Gender Differences Of Human Response Under Vibration Condition -- 23 Extended Kalman Filter (EKF) With Sensitive Equation For The PEMFC Internal State Estimation -- 24 Global Localization And Position Tracking Of Autonomous Transport Vehicles -- 25 An Intelligent Flow Measurement Technique By Venturi Flowmeter Using Optimized Ann -- 26 Efficient Video Streaming Over Wireless Mesh Networks.
Keywords: Engineering; Computer communication systems; Applied mathematics; Engineering mathematics; Computational intelligence; Control engineering; Robotics; Mechatronics; Engineering; Control, Robotics, Mechatronics; Computer Communication Networks; Appl.Mathematics/Computational Methods of Engineering; Computational Intelligence; Electronic books